The Influence of Culture on Consumer Impulsive Buying Behavior - Kacen, Jacqueline J.; Lee, Julie Anne (Journal of Consumer Psychology, 2002)
This DOI is not currently attached to any metadata records. DOIs can’t actually ever be deleted (they’re persistent), but sometimes our members create DOIs in error. We do have a process to approximate deletion which we follow only in rare cases where the DOI has been genuinely created in error, and most crucially, if the DOI has never been published anywhere online or in print and never otherwise distributed to or communicated with anyone (authors, readers, reviewers, etc.